Implementation of a Multidisciplinary Team Approach and Fish Oil Emulsion Administration in the Management of Infants with Short Bowel Syndrome and Parenteral Nutrition-Associated Liver Disease. (2012) - Sant'Anna, Ana MGA; Altamimi, Eyad; Clause, Rose-Frances; Saab, Joanne; Mileski, Heather; Cameron, Brian; Fitzgerald, Peter; Sant'Anna, Guilherme M
Abstract : OBJECTIVE: To describe the authors' experience with the implementation of a multidisciplinary approach and use of fish oil emulsion (FOE) in the management of infants with short bowel syndrome (SBS) and parenteral nutrition-associated liver disease (PNALD). METHODS: Between August 2006 and June 2009, four cases of SBS and severe PNALD were managed by the team using specifically developed protocols. The FOE was initiated if serum direct bilirubin levels were ≥100 μmol/L. To quantify the degree of exposure to high serum direct bilirubin levels over time, the area under the curve (AUC) for each patient was calculated before and after initiation of FOE. Linear regression analyses were performed to evaluate correlations between the AUC, duration of cholestasis and initiation of FOE. RESULTS: All patients survived and no complications were observed during the study period. After the first patient, FOE was initiated progressively earlier, but poor correlation between the AUC before and after its introduction was observed (r 2 =0.41924). However, there was strong correlation between the duration of PNALD before FOE initiation and time to resolution (r 2 =0.72133): the earlier the FOE was initiated, the shorter the time to resolution. CONCLUSION: The authors report a positive experience with the implementation of a multidisciplinary approach and the use of FOE in infants with SBS and severe PNALD. The earlier the FOE was initiated during the cholestatic process, the shorter the time to resolution. The present study is a hypothesis generator, raising the question of whether an earlier introduction of this particular therapy can effectively shorten the cholestasis process in these patients.